EVALUASI TINGKAT RISIKO PEMBIAYAAN MURABAHAH - EKA P Y A, NUR (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract :This research aim to evaluation level of murabahah financing risks. This research used qualitatif research by descriptive approach will be present trianggulasi methode, observation technical data, documentation, and interview. This result shows that evaluation level of murabahah financing risks at BPRS XYZ, steps and prosedur that is simple steps and the most favorite finance. The problems at financing derives to internal factors (bank), internal factors (customer), and eksternal factors. The way to minimize the level of financing risks is by detecting on collectability level in order to get the information. And the steps already succes so there will be rescheduling process, reconditioning, restructuring, assits management and liquidation. Keyword : bank, financing risks, murabahah